Solutins of Systems for the Linear Fredholm-Volterra Integral Equations of the Second Kind - Omran, H. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we present some numerical methods for solving systems of linear FredholmVolterra integral equations of the second kind. These methods namely are the Repeated Trapezoidal Method (RTM) and the Repeated Simpson’s 1/3 Method (RSM). Also some numerical examples are presented to show the efficiency and the accuracy of the presented work.